Овруцький варіант епігравету Східної Європи - Залізняк, Л.Л. (Археологія, 2017)
Стаття присвячена нещодавно окресленій групі своєрідних верхньопалеолітичних пам’яток Овруцького кряжа, що на півночі Житомирщини. Підсумовуються результати дослідження палеоліту Овруччини протягом ХХ та початку ХХІ ст. The group of hunters’ sites of the end of the glacial epoch is inspected on Ovruch plateau in Zhytomyr region by the Expedition of the Institute of Archaeology of the Ukrainian National Academy of Sciences under L.L. Zaliznyak’s direction in 2016. Zhelon, Zhelon 2, Zhelon 3, Hayevychi, Pishchanytsia, and Kosuli sites were discovered a few years before by the Ovruch Expedition of the IA NASU under the direction of A.P. Tomashevskyi. Flint artefacts were deposited on arable surface of plateau’s ridge in north-eastern part of Ovruch range over 6,0—7,0 km along the plateau’s ridge above OvruchSlovechno road. The new perspective Kelembet site with an expressive collection of Epigravettian type flint was discovered and inspected when the expedition studied the sites for the second time in 2016. The geological position of artefacts (directly under the modern soil), as well as the typology of tools, allow the author to preliminary date the finds back to the Final Palaeolithic, approximately 14—12 thousand years ago, that is to the period of mammoths’ extinction inEurope.The sites presented a standard flint inventory ofEpigravettian type.The finds’repeatability gives grounds for supposition that the sites were left by kin groups of hunting population who periodically returned to traditional places of seasonal nomad camps. The author assumes that sites mentioned were left by the hunters specialized on mammoths and other gregarious herbivorous species of the Ice Age steppe. Repeated finds of corresponding fauna bone remains in ravines located near the sites testify for that. In particular, a mammoth’s tusk with a chevron pattern engraved on it was found in a ravine near Klynets Village by V.A. Mesiats in 1955. There is a reason to state not only that the known today Final Palaeolithic sites in Ovruch region were synchronous and belonged to a single culture, but also that they belonged to a single original Ovruch local variant of Epigravettian, which is dated by the Final Palaeolithic period, about 14—12 thousand years ago. EpigravettianpopulationfromNorthUkrainedisappearedsuddenly intheperiodoftheEuropeanmammothpopulation’s extinction about 13—12 thousand years ago, not having left genetic descendants. The historic destiny of Epigravettian mammoth hunters in Northern Ukraine remains to be an unsolved problem of Ukrainian Palaeolithic. Экспедицией ИА НАНУ в 2016 г. под руководством Л.Л. Зализняка обследована группа стоянок первобытных охотников конца ледниковой эпохи на Овручском плато на Житомирщине. Стоянки Желонь, Желонь 2, Желонь 3, Гаевичи, Песчаница, Косули открыты несколько лет назад Овручской экспедицией ИА НАНУ под руководством А.П. Томашевского. Кремневые изделия залегали на перепаханой поверхности гребня плато в северо-восточной части Овручского кряжа, на протяжении 6,0—7,0 км вдоль северо-восточного края плато над дорогой Овруч— Словечно. При повторном обследовании памятников экспедицией 2016 г. найдена и обследована новая перспективная стоянка Келембет, из которой происходит выразительная коллекция кремня эпиграветтского типа. Условия залегания артефактов (непосредственно под современной почвой), а также типология изделий дают основания предварительно датировать находки финальным палеолитом, приблизительно 14—12 тыс. лет назад, то есть порой вымирание мамонтов в Европе. Стоянки дали стандартный кремневый инвентарь эпиграветтского типа. Однотипность находок дает основания для предположения, что памятники были оставлены родственными группами охотничьего населения, которые периодически возвращались на традиционные места сезонных стойбищ. Допускаем, что упомянутые памятники оставлены охотниками на мамонтов и других стадных травоядных приледниковья. Об этом свидетельствуют неоднократные находки соответствующей фауны в соседних со стоянками оврагах, в частности бивня мамонта с выгравированным елочным орнаментом из оврага вблизи с. Клинець, найденного В.А. Месяцем в 1955 г. Есть основание утверждать не только о синхронности и однокультурности известных в настоящее время финальнопалеолитических памятников Овруччини, но и об их принадлежности к одному своеобразному овручскому локальному варианту эпиграветта, что датируется финальным палеолитом, около 14—12 тыс. лет назад. Эпиграветтское население севера Украины исчезло внезапно в период вымирания европейской популяции мамонтов около 13—12 тыс. лет назад, не оставив после себя генетических потомков. Историческая судьба эпиграветтских охотников на мамонта севера Украины остается нерешенной проблемой палеолита Украины.